Analysis of clinical symptoms and ABCC6 mutations in 76 Japanese patients with pseudoxanthoma elasticum. Issue 6 (10th February 2017) - Iwanaga, Akira; Okubo, Yumi; Yozaki, Mariko; Koike, Yuta; Kuwatsuka, Yutaka; Tomimura, Saori; Yamamoto, Yosuke; Tamura, Hiroshi; Ikeda, Satoshi; Maemura, Koji; Tsuiki, Eiko; Kitaoka, Takashi; et al.
Abstract: Pseudoxanthoma elasticum (PXE) is a hereditary disease, causing calcification and degeneration of elastic fibers, which affects the skin, eye, cardiovascular systems and gastrointestinal tract. PXE is caused by mutations in the ABCC6 gene. Neither detailed nor large‐scale analyses have been accomplished in Japanese patients with PXE. We, therefore, investigated clinical symptoms and ABCC6 gene mutations in 76 Japanese patients. Japanese PXE patients ( n = 76) had a significantly lower incidence of vascular lesions than 505 PXE patients in the Leiden Open Variation Database (LOVD) (38.7% vs 65.1%, respectively; P = 1.34E‐06); however, the incidences of the skin, eye, cardiac and gastrointestinal lesion symptoms were not significantly different. Symptom severity scores for skin, eye and vascular lesions, calculated using the Phenodex™ system, were significantly lower in Japanese PXE patients than in LOVD PXE patients. Genetic analysis revealed three nonsense, four frame‐shift, one exon deletion and 13 missense mutations in ABCC6 in 73 patients; however, we were unable to detect pathogenic mutations in three patients. Frequent mutations differed between Japanese and LOVD PXE patients. In Japanese PXE patients, the top five mutations accounted for more than 60% of all pathogenic changes, suggesting the presence of founder effects. Consistent with previous reports, no obvious correlations between genotypes and phenotypes were identified in this study. In conclusion, we consider that the milder clinical phenotypes, observed even in older Japanese PXE patients, could be attributed to environmental factors such as dietary habits and lifestyle, as well as genetic background.